PEMBERDAYAAN INDUSTRI KECIL YANG BERBASIS AGROINDUSTRI DI PEDESAAN - BUDIARTO BUDIARTO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2008)
Indonesia economics now can not based on high technology, but industrialization with agricultural sector based. Agroindustry be answer correctest, because has dependability rear (backward linkage) and dependability forwards (forward linkage) for long time.